The difficulties that beset senior high school students in research writing and presentations - Joseph B. Quinto; Girlie C. Jimenez; Illuminada Simbulan Menzi (Institute of Advanced Engineering and Science, 2026)
Writing and presenting research are endeavors that senior high school students have to hurdle in the Philippines. Therefore, this research aimed at unravelling the dimensions of the difficulties faced by senior high school students in their research writing and research presentations through a sequential qualitative mixed-methods design. Primary data was gathered through a qualitative survey of 448 students, while secondary data was obtained via 10 focus groups with 7-10 members representing the different strands in one private senior high school in Baguio City, Philippines. All these participants were selected using combined quota and purposive sampling. Thematic analysis coupled with an iterative procedure was utilized to treat the harvested qualitative data. Findings revealed that the dimensions of the difficulties faced by student-researchers in research writing are health-related, manuscript-related, people-related, and resources-related, while the dimensions in research presentations are inner-directed and outer-directed. This research adds to the current body of knowledge, can contribute to achieving the United Nations sustainable development goal 4.5 and 4.7 on equal education access and global citizenship skills, and recommends research trajectories.